More than just Biological Sex: Examining the Structural Relationship between Gender Identity and Information Search Behavior - Ramkissoon, Haywantee; Nunkoo, R. (Sage Publications, 2012)
The influence of gender on travelers’ information search behavior continues to attract the attention of researchers. However, most scholars have studied gender differences from a biological perspective, treating gender as a unitary theoretical concept. This article challenges such an approach and argues for a more differentiated perspective to the study of gender differences in information search behavior. It approaches gender differences from a psychological perspective and proposes that the travelers’ gender identity (masculinity and femininity) is a determinant of their search behavior. The gender schema theory and the selectivity theory inform the model of the study. Five hypotheses are developed and are tested using responses collected from 568 tourists. Results from the structural equation modeling analysis indicate support for all hypotheses, confirming that gender identity is a good determinant of travelers’ search behavior. Travelers displaying high femininity traits were found to engage in more internal as well as external information search. Respondents with high masculinity traits relied less on both internal and external search for information. The theoretical and managerial implications, as well as the limitations of the study are discussed. The study also provides some directions for future research.